(untitled) (Journal of Philosophy Culture and Political Science, 2022)
An in-depth analysis of the process of the spiritual development of humankind shows that "homo sapiens" has always sought to find certain meanings of its existence, for example, the so-called ultimate foundations of being. This desire determines the nature of man. Among all creation, only man seeks to transcend his own existence. The results of this transcending are reflected in mythology, religion, and philosophy. In these types of worldviews, human consciousness reflects the essential characteristics and properties of being in various forms of cognition. A person’s extreme views and ideas about himself or herself and the world around him or her are formulated in the universals of culture or philosophical categories. The natural environment, in which it lives, economic activity and social relations that develop in the course of this activity influence the understanding of the world and worldview of each nation. Despite the fact that emotional and figurative elements predominate in the mythological worldview, the presence of a rational and logical beginning in it cannot be ruled out. Therefore, many philosophical ideas and reflections mature in the context of a mythological worldview. In this regard, it is important to determine the essence and cognitive role of worldview (cultural) universals in the transitional stages, in the "crossings of thinking" from mythology to pre-philosophical reasoning. This helps to clarify the essence of the early philosophical ideas of the Indian and Kazakh people about the relationship of the spiritual and material principles in the universe, matter and energy, time and space, substance and accidents, as well as these universals reflected in the national mentality and their role in the formation of Onto-Axiological ideas. Keywords: mythology, proto philosophy, substance, cosmic energy, substance, randomness, time, space.